Gender identification as a factor of harmonization of social relations and living space personality - Falko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with the psychological mechanisms of gender identification. Analyzes approaches to overcome gender stereotypes. Examines the impact of gender identity on the harmonization of social relations.
Keywords: gender; gender identity; gender stereotype